Development of a microchannel heat sink for thermal management - Yeo, Wei Long (2019)
With the rapid development in the electronic industry, the sizes of majority of the electronic devices (e.g. VLSI systems, LEDs, micro reactors, etc.) have undergone significant reduction. Due to their minute sizes, effective dissipation of the heat accumulated in the electronic chips has become a challenging task, since failing of doing so, may cause reliability issues to the devices. Microchannel heat sink (MCHS) is found to provide the most reliable cooling technology compared to conventional heat sink due to its small size, low coolant requirements and its superior command over heat carrying capability provided by small hydraulic diameter. Here, MCHSs with extended surface technique were investigated numerically and experimentally in terms of fluid flow and heat transfer characteristics. A three-dimensional MCHS model was drawn and simulated using Ansys Fluent. The simulation and experimental result of MCHS with extended surface was compared to rectangular MCHS. This study focuses on Reynolds number less than 1200 which is in laminar flow. The collected result shows that the extended surface technique enhances the heat transfer performance. The presence of micro-fins helps to disrupt the thermal boundary layer and also increases the pressure drop. The validation result indicates that the existence of micro-fins significantly enhances the heat transfer performance. The designs of various geometries micro-fins ware introduced and studied in the modelling part. The average wall temperature and Nusselt number are calculated and plotted with respect to the Reynolds number at heat flux equals 100 W/cm2. The result shows that micro-fins with diverging cylindrical geometry incorporated with triangular ribs (Case E) perform well at Reynolds number less than 700; whereas those incorporated with semi-circle ribs (Case C) are suitable for Reynolds number more than 700.